OUTCOMES OF SURGICAL MANAGEMENT OF FRACTURE PENIS: EXPERIENCE FROM A TERTIARY CARE HOSPITAL IN BANGLADESH - Md. Selim Morshed; AKM Musa Bhuyian; Mohammad Saruar Alam; Md. Towhid Belal; Sayem Hossain; Mohammad Ibrahim Ali; Sojib Bin Zaman (Public Health of Indonesia)
Background: Penile fracture is an emergency and uncommon presentation to the urology department. Immediate surgical repair can be a standard of care for patients with penile fracture.